ANALISIS EFISIENSI FAKTOR PRODUKSI USAHATANI JAGUNG PIPILAN KERING DI DESA GEMIUNG KECAMATAN BUANA PEMACA KABUPATEN OGAN KOMERING ULU SELATAN - sutra alam; Septianita Septianita (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2023)
Based on the formulation of the problem stated, the purpose of this research is to analyze the factors that influence dry shelled corn farming production and production efficiency of dry shelled corn farming in Gemiung Village, Buana District, South Ogan Komering Ulu Regency. The research was conducted in one of the corn producing centers in Gemiung Village. The number of samples taken in this study were 30 farmer owners and cultivators. The analytical tool used in this study is the regression of the Cobb Douglas type production function whose calculations use multiple linear regression equations. From the results of the analysis of the factors that influence the production of dry shelled corn in Gemiung Village, namely land area (X1), seeds (X2), pesticide fertilizers (X4) and labor (X5) with a coefficient value of 0.998 or 99.8%. and the value of efficiency in dry shelled corn farming, namely land area (X1) 24.59, seeds (X2) 4.8, no efficiency (> 1) in the use of inputs, it is necessary to reduce the amount for each input while for fertilizer (X3) 0.00, pesticides (X4) -62.8 and labor (X5) 0.01 are said to be inefficient (<1) in the use of inputs, it is necessary to increase the amount for each input used.Keywords: Factors, production, corn, efficiency, farming